A RELAÇÃO ENTRE A PRISÃO PREVENTIVA E A GARANTIA CONSTITUCIONAL DA PRESUNÇÃO DE INOCÊNCIA (Reflection and Critique Law Magazine, 2025)
The work was developed with the aim of critically analyzing the institute of pre-trial detention in the Brazilian legal system, given that a significant portion of the prison population is made up of pre-trial detainees, based on a review of the literature on the subject. To begin with, we intend to analyze the institute of pre-trial detention and its foundations, as well as its periodic review and possible revocation, and then bring in the constitutional guarantee of the presumption of innocence, correlating them. An analysis will also be made of the absence of a maximum limit for the duration of pre-trial detention, reading the principle of the presumption of innocence as proportionality in order to differentiate between procedural detention and detention to serve a sentence.